Raman spectroscopic study of ZnO/NiO nanocomposites based on spatial correlation model - Dev, S.G.; Sharma, Vikas; Singh, Ashish; Baghel, Vidushi Singh; Yanagida, Masatoshi; Nagataki, Atsuko; Tripathi, Neeti (Royal Society of Chemistry, 2019)
The effect of nickel concentration has been investigated in ZnO/NiO nanocomposites synthesized using the co-precipitation method. The X-ray diffraction and TEM measurements confirm the distinct phase of NiO in the ZnO/NiO samples. Furthermore, the Raman study shows the sharp modes at 99 cm-1 and 438 cm-1 corresponding to E(low)2, E(high)2 of hexagonal wurtzite ZnO structure and, 1080 cm-1 associated to the two-phonon (2P) mode of NiO, respectively. We also compared the effect of Ni concentration on the formation of ZnO/NiO by analyzing Ehigh2 Raman mode of ZnO with the help of spatial correlation model. The correlation lengths, broadening and asymmetry ratio obtained from the fitting showed good agreement with the experimental results. This journal is © The Royal Society of Chemistry.
Keywords: Raman spectroscopic study; Spatial correlation models; Study of ZnO/NiO; Nanocomposites